Pedagogy and barbarity. The Auschwitz children's literature as an education reference (Encuentros, 2023)
Auschwitz children's literature is understood as a formation reference (Bildung). This offers testimony of the barbarism of the concentration and extermination camps and questions the idea of ​​man as being for the good. The experience of barbarism, what man does to man, shows the indeterminacy of human life. The unspeakable character of barbarism leads to a philosophical approach in which, following Benjamin, the remembrance of the past broadens the interpretative possibilities of the present. It is concluded that what is formative in the children's literature of Auschwitz is not the prescription of the duty of man, but the affirmation of the duty of memory that challenges every formative process.
Keywords: child literature; Auschwitz; formation; memory; pedagogy